Indoor location estimation utilizing Wi-Fi Signals - Hashim, Nik Mohd Zarifie; Zahari, Muhammad Khairul; Ja'afar, Abd Shukur; Salleh, Azahari; Darsono, Abd Majid (The World Academy of Research in Science and Engineering, 2020)
Global Positioning System is commonly been used for locating a position of a specific structure in finding geographical coordinates of a target area. Though, this application is still having a restricted in term of the signals, might not well operated and ineffective for indoor usage. The study aim is to develop positioning and localization systems by using Wi-Fi signal. Estimation was made based on the measurement of wireless distance for estimation the user’s coordinates. Analysis of views called the fingerprint algorithm is used in this study. The algorithm involved two phases over an offline and the online phases of the survey. Unidentified user’s coordinates will be in the online phase by comparative databases collected in the survey phase. MATLAB Graphical User Interface and Android has been used to develop a user interface for simulation purposes. Several analyses were performed to define the precision and efficiency of occurred error as the number of access points and the traffic environment. Finally, the user required to provide several inputs e.g. the exact location and the RSS from AP’s number at the present location. The simulation-based software will evaluate the estimation location and positioning of the user and will match to user’s precise location.